The Transformation of the Cupak Gerantang Folklore of Lombok into Child-Friendly Digital Comic Characters with Moral Values - Gozin Najah Rusyada; Nurul Kemala Dewi; Muhammad Tahir; Irfan Hidayat (Gorga : Jurnal Seni Rupa, 2025)
Cupak Gerantang is a traditional folktale from Lombok that tells the story of two young men, Cupak and Gerantang. The narrative emphasizes the importance of avoiding negative traits and practicing virtuous behavior, making it a potential medium for promoting character education from an early age. However, the folklore faces several limitations, including limited audience reach, lengthy performance duration, use of local language, and visualizations that are less suitable for children. To address these challenges, this study aimed to adapt the Cupak Gerantang folktale into child-friendly digital comic characters. The research employed a design-based approach by adapting the vehicle transfer model, which consists of four stages: (1) ekranization, transferring characters and moral values into narrative and visual designs; (2) shrinkage, simplifying story elements and adjusting visuals to suit children; (3) addition and variation, modifying the storyline, setting, characterization, and visual style to enhance appeal; and (4) limited trials with 15 elementary school students. The trial results showed that most students responded positively to the illustrations, color schemes, and plot, confirming that the moral values had been effectively conveyed, and they expressed interest in reading the complete digital comic version. These findings suggest that the development of digital comic adaptations of characters from local folklore has potential as an innovative educational medium to support character education and foster appreciation for local wisdom in the digital age.